DIGITAL LEADERSHIP AND ORGANIZATIONAL TRANSFORMATION IN THE PUBLIC SECTOR - Marliza Oktapiani (Alqaprint Jatinangor, 2025)
This study explores the critical intersection between digital leadership and organizational transformation within the public sector through a comprehensive literature review. The research synthesizes current scholarly findings to identify how digital leadership facilitates innovation, adaptability, and service efficiency in bureaucratic institutions. By examining theoretical and empirical sources published in the past decade, the study highlights the pivotal competencies, behaviors, and strategies that enable leaders to navigate digital disruption. The review underscores that effective digital leadership transcends technical proficiency, requiring vision, agility, and cultural transformation. Findings reveal that leadership commitment and organizational readiness are decisive factors in the success of digital initiatives. Moreover, digital transformation in the public sector remains constrained by structural rigidity and limited digital capabilities. The synthesis offers insights into how strategic leadership practices can overcome these barriers. This study contributes to understanding the evolving role of leadership in modern governance. It provides a conceptual foundation for future research on sustainable digital transformation in public institutions.